Urban expansion and open spaces: dynamics, influences and conflicts in the conformation of the landscape of the South Zone of Bauru-SP - Rossi, Mariana [UNESP]; Mattos, Karina Andrade [UNESP]; Truppel Constantino, Norma Regina [UNESP] (Fiam-faam Centro Univ, 2019)
Over the last decades, new dynamics of urban landscape production and transformation have influenced on the character of their open spaces. Processes such as the fragmentation and the dispersion of the urban fabric, which include the fast proliferation of gated communities, have contributed to the increase of insecurity and abandonment of the free access open spaces, damaging the social dynamics of public character. This paper aims to highlight the benefits that these spaces could provide for the city if, instead of being treated as isolated fragments, they were thought of as a system, that is, as a set of elements integrated with the urban planning strategies. From the results of a research carried out in the city of Bauru-SP, are analyzed the transformations that open spaces have been suffering owing to the new forms of organization of the urban fabric with tendencies to privatization, especially in recent urban sprawl areas.
Keywords: urban open spaces systems; dispersed and fragmented urbanization; privatization of urban space; gated communities; Bauru